Kunstcollectie Gemeente Heerlen : catalogus - Defesche, D.; Wintgens, D. (Heerlen : Stad Heerlen)
Bartels, Harrie ; van de Beek, Felix ; Berserik, Herman ; van Bohemen, Kees ; Brands, Eugene ; Brouwer, Ger ; Constant ; Corneille ; Defesche, Pieter ; Diederen, Jef ; van Drumpt, Hans ; Eyck, Charles ; Giesen, Hans ; Gijsbers, Gijs ; etc.
Nederlands
boek